2023
DOI: 10.1002/ange.202300046
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian‐like Flexible Organic Crystal Optical Fibers for Underwater/Air Micro‐Precision Lighting and Sensing

Abstract: Visible light guiding optical fibers with underwater operational capability are highly desired for subaquatic communication and sensing technologies. Herein, we present mechanically flexible, blue‐violet fluorescent (4,4′‐bis(2,6‐di(1H‐pyrazol‐1‐yl)pyridin‐4‐yl)biphenyl) (BPP) crystal waveguides with high‐aspect ratio. These milli‐meter‐long BPP crystals guide light actively and passively in ambient and underwater conditions demonstrating their amphibian‐like character. Due to the crystal's high flexibility, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Under the light excitation in air (Figure a), the MCW exhibits typical characteristics of the PL waveguide with a much brighter emission at its two terminals and a relatively weak emission in the middle . After immersing the MCW in a buffer solution containing TPrA, the PL intensity in the middle part turns strong at the cost of that at two terminals (Figure b) . By plotting the grayscale variation of PL intensity along the longitudinal axis of MCWs (Figure d), we can see clearly that the PL intensity of the middle part of the MCW (yellow line) is about twice larger than that in air (cyan line).…”
Section: Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Under the light excitation in air (Figure a), the MCW exhibits typical characteristics of the PL waveguide with a much brighter emission at its two terminals and a relatively weak emission in the middle . After immersing the MCW in a buffer solution containing TPrA, the PL intensity in the middle part turns strong at the cost of that at two terminals (Figure b) . By plotting the grayscale variation of PL intensity along the longitudinal axis of MCWs (Figure d), we can see clearly that the PL intensity of the middle part of the MCW (yellow line) is about twice larger than that in air (cyan line).…”
Section: Results and Discussionmentioning
confidence: 93%
“…53 After immersing the MCW in a buffer solution containing TPrA, the PL intensity in the middle part turns strong at the cost of that at two terminals (Figure 2b). 54 By plotting the grayscale variation of PL intensity along the longitudinal axis of MCWs (Figure 2d), we can see clearly that the PL intensity of the middle part of the MCW (yellow line) is about twice larger than that in air (cyan line). Moreover, the PL intensity ratio between the terminal and middle of MCW in air (namely, 17191/2491) is 2.6 times larger than that in solution (namely, 12978/4876) for the left terminal, while it is 3.9 times for the right one.…”
Section: ■ Introductionmentioning
confidence: 94%
“…In addition, Chandrasekar et al demonstrated the amphibious, air/submersible compatible optical waveguide properties of highly flexible millimeter-long BPP crystals. 107 Hydrophobic flexible crystals BPP as amphibian-like, millimeter-long organic optical fibers can effectively transmit and deliver visible light signals as microprobes under water (Figure 21). The microtip of the submerged fiber can be mechanically reconfigured to direct the optical output as a probe to the desired target with micrometer-scale precision.…”
Section: Microscale Organic Photonic Integrated Circuitsmentioning
confidence: 99%
“…From drilling wood to making fire, to inventing electric light, to exploring advanced light sources in the microcosm, human beings have never stopped chasing light. Organic fluorescent materials (OFMs) have attracted attention due to their wide applications in chemical sensing, cell imaging, optoelectronic display, drug delivery, anticounterfeiting printing, etc. Traditional organic light-emitting compounds rely on polycyclic aromatic hydrocarbons or alternating single-multiple bonds and other large conjugated structures to achieve fluorescence emission. According to the emission characteristics, they can be divided into two categories: aggregation-caused quenching (ACQ) , and aggregation-induced emission (AIE). , However, in recent years, a class of compounds containing electron-rich atypical chromophores such as amino groups, hydroxyl groups, carbonyl groups, ester groups, anhydride groups, sulfonic acid groups, and cyano groups exhibit unexpectedly bright fluorescence in the aggregated state. , Different from traditional aromatic ACQ luminescence, the unconventional luminophore has the inherent advantages of more application scenarios and large-scale production possibilities thanks to its simpler structure.…”
Section: Introductionmentioning
confidence: 99%